Autonomous Vessels in Maritime Affairs
XXX, 410 p. 18 illus., 11 illus. in color.
Keywords: This book examines law and governance implications in relation to maritime autonomous surface ships (MASS). Adopting a multi-disciplinary approach, it focuses on a wide array of timely, topical and thorny issues, including naval warfare and security, seaworthiness and techno-regulatory assessments, global environmental change, autonomous passenger transportation, as well as liability and insurance. It also considers selected national and regional developments. The book provides an insight into the role of innovation-diplomacy as the driving force that could expedite the transition from automation to autonomy. After navigating through the complex law and governance landscape, it concludes by assessing critical findings for further consideration. The book will appeal to scholars and students of maritime technology, law and governance. Tafsir Matin Johansson is Assistant Professor at the World Maritime University, Sasakawa Global Ocean Institute, Sweden. Jonatan Echebarria Fernández is Honorary Lecturer at The City Law School, City, University of London, UK. Dimitrios Dalaklis is Professor at the World Maritime University, Sweden. Aspasia Pastra is a Post-Doctoral Fellow and Maritime Policy Analyst at the World Maritime University, Sasakawa Global Ocean Institute, Sweden. Jon A. Skinner is Adjunct Professor at Mat-Su College, University of Alaska Anchorage, and an instructor at the Graduate College of Professional Military Education, Air University, USA. Chapter 11 and Chapter 18 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.